KODE ETIK DIY ( DO IT YOURSELF)PUNK - , Fajar Radite, Dr. Aris Arif Mundayat ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This thesis takes the form of a continuation and expansion of an earlier work by the author on the punk genre/subculture. This thesis focuses on the construction of political identity in subcultures. The object, the punk community Taring Babi (meaning âthe pigs tusksâ) has been based in the south of Indonesiaâs capital city Jakarta for nearly 15 years, and functions and operates according to an economic model based on the ethical code of âDo it yourselfâ (or DIY). This economic model has been developed and implemented by the collective as an expression of their disagreement and rejection of mainstream capitalist economic models. This thesis has been based on interviews and observations made with the collective Taring Babi in Jakarta, between March and April 2011. It takes the form of a qualitative research project comprised of technical analysis of data using the descriptive analytical method. The author has attempted to provide a clear description of âfield factsâ concerning the object and their alternative DIY based economy. FINDINGS: In all aspects of Taring Babiâs DIY based economic model, the punk identity continues to plays an overlyingly dominant role, suggesting that this model not only reflects but also strengthenâs the groupâs punk identity. Taring Babi has been able to implement and power this economy by utilising concepts of community and collectivity. Furthermore, the DIY economic model takes the form of a successful and in many ways potentially sustainable solution to social dissatisfaction. However, itâs weakness lies in that this system has been adopted from and is thus dependent upon principles of punk culture that have been laid down in the West, and is thus Taring Babi have yet to move on or develop beyond these Western reference points. CONCLUSION: Uniquely, the DIY discourse has come to accentuate and define the groupâs political identity in two ways